2003
DOI: 10.1523/jneurosci.23-15-06245.2003
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Subtypes Involved in the Presynaptic and Postsynaptic Actions of Dopamine on Striatal Interneurons

Abstract: By stimulating distinct receptor subtypes, dopamine (DA) exerts presynaptic and postsynaptic actions on both large aspiny (LA) cholinergic and fast-spiking (FS) parvalbumin-positive interneurons of the striatum. Lack of receptor- and isoform-specific pharmacological agents, however, has hampered the progress toward a detailed identification of the specific DA receptors involved in these actions. To overcome this issue, in the present study we used four different mutant mice in which the expression of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
184
4
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(204 citation statements)
references
References 72 publications
14
184
4
1
Order By: Relevance
“…With this method, a presynaptic D 2 -mediated modulation similar to that shown on the striatopallidal pathway (Cooper and Stanford, 2001;Mengual and Pickel, 2002) or in the cholinergic or fastspiking (FS) interneurons (Pisani et al, 2000;Momiyama and Koga, 2001;Centonze et al, 2003) was shown. Similarly, a presynaptic modulation by D 1 receptor agonists as that reported in the striatonigral pathway (Floran et al, 1990(Floran et al, , 1997Cameron and Williams, 1993;Radnikow and Misgeld, 1998) was also shown, despite postsynaptic dopaminergic actions (Pacheco-Cano et al, 1996) on the subthreshold inward rectification Nisenbaum and Wilson, 1995;Mermelstein et al, 1998;Farries and Perkel, 2000) that shunts inhibitory inputs (Fitzpatrick et al, 2001).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…With this method, a presynaptic D 2 -mediated modulation similar to that shown on the striatopallidal pathway (Cooper and Stanford, 2001;Mengual and Pickel, 2002) or in the cholinergic or fastspiking (FS) interneurons (Pisani et al, 2000;Momiyama and Koga, 2001;Centonze et al, 2003) was shown. Similarly, a presynaptic modulation by D 1 receptor agonists as that reported in the striatonigral pathway (Floran et al, 1990(Floran et al, , 1997Cameron and Williams, 1993;Radnikow and Misgeld, 1998) was also shown, despite postsynaptic dopaminergic actions (Pacheco-Cano et al, 1996) on the subthreshold inward rectification Nisenbaum and Wilson, 1995;Mermelstein et al, 1998;Farries and Perkel, 2000) that shunts inhibitory inputs (Fitzpatrick et al, 2001).…”
Section: Discussionmentioning
confidence: 82%
“…A dopaminergic modulation should be seen as consistent, however, even after intrastriatal field stimulation, if its presence is somehow ubiquitous or predominant (Pisani et al, 2000;Mo-miyama and Koga, 2001;Centonze et al, 2003). Otherwise, modulation would be concealed by the mixed source of differentially modulated inputs (Fitzpatrick et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favoring the second option is the report that, after binding to D 2 receptors, dopamine can be internalized to form a signaling complex (including ß‐arrestin and protein phosphatase 2) that regulates the Akt pathway (Beaulieu et al, 2008), a cascade involved in neuroprotection (Dudek et al, 1997; Soler et al, 1999). Dopamine inhibits GABA A ‐mediated synaptic inputs to intrinsic striatal neurons (Bracci, Centonze, Bernardi, & Calabresi, 2002; Momiyama & Koga, 2001; Pisani, Bonsi, Centonze, Calabresi, & Bernardi, 2000) through presynaptic D 2 receptors (Centonze et al, 2003; for a review, see Berke, 2011). All together, we speculate that dopamine could be involved in the acute and chronic protection of FS striatal terminals and, therefore, could contribute to long‐term FS survival.…”
Section: Discussionmentioning
confidence: 99%
“…This brain area receives profuse dopaminergic innervation arising from midbrain DA neurons and has a very high density of DA receptors (Mansour and Watson, 1995;Surmeier et al, 1996;Centonze et al, 2003). Cocaine increases DA release in the striatum through the blockade of transporter-mediated DA reuptake from nigrostriatal nerve endings and causes rapid induction of striatal c-fos, a commonly used molecular marker for neuronal activity.…”
Section: Involvement Of the Striatum In Cocaine Addictionmentioning
confidence: 99%